(untitled) (Scientific journal of the Fergana State University, 2023)
This article shows that the US wants the region to act as an independent entity in international relations, while strengthening its activity in Central Asia with this new strategy. Currently, in the process of global changes, the US’s ideological development path and its uniqueness Opinions about it are stated.